Diabetes mellitus na gestação: prevalência, desfechos das induções e caracterização das gestantes e recém-nascidos atendidos no Hospital Universitário de Santa Maria - Barros, Giana Nunes Mendonça de (2020)
Diabetes mellitus (DM) during pregnancy is an unfavorable environment for embryonic and fetoplacental development and is the most common metabolic disorder in pregnancy. Due to its repercussion, it is necessary to assess its prevalence, characteristics of pregnant women with this pathology and perinatal outcomes. In addition, the question is raised whether there is an increase in the rates of cesarean sections, due to early labor induction, a practice adopted at Hospital Universitário de Santa Maria (HUSM).The objective of this study was to study the prevalence of DM in pregnancy, characterize diabetic pregnant women treated at HUSM and to analyze the gestational outcomes of these pregnant women and newborns. This study included 885 patients who delivered at HUSM between January 2017 and January 2018, with review of medical records. Data on pregnant women, prenatal care, pregnancy outcome, puerperium and data from newborns were evaluated. A descriptive analysis of the quantitative variables was performed and for the qualitative variables, the chi-square test was used, with a significance level of 5%. The study respected the ethical precepts contained in the National Health Council Resolution nº466 / 2012, the same is an addendum to the Evolution and Outcome of Pregnancy Project monitored at HUSM. The prevalence of diabetes in pregnancy was 13.1%, which is below the average of national and global prevalence. Most diabetic pregnant women received prenatal care, pregnancy complications presented, held over 6 consultations, gestational age over 37 weeks, did not go into labor, and the most frequent mode of delivery was cesarean. As for newborns, when compared to non-diabetic mothers, they had no higher rate of complications, Intensive Care Unit admissions and macrosomia. There was a significant association of diabetes with multiparity. Regarding the mode of delivery, the study showed an increase in cesarean section rate among patients with diabetes. However, it did not confirm the hypothesis that cesarean sections occurred after unsuccessful labor inductions. Further studies are needed to determine the optimal time of birth of diabetic mother's child, since complications of newborns of mothers with diabetes mellitus during pregnancy is confirmed.